Revitalising Waqf Institutions Through A Cocreation Ecosystem Of Public Engagement - Fuadah Johari; Noraini Yusuff; Nor Syahidah Ishak; Hanim Hj Misbah; Siti Latipah Harun; Nurul Adilah Hasbullah; Siti Hajar Salwa Ahmad Musadik; Azuan Ahmad (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA